The Cost Channel of Monetary Policy : Further Evidence for the United States and the Euro Area - Rabanal, Pau (IMF Working Papers; Working Paper ;, 2003)
This paper estimates the importance of the cost channel of monetary policy in a New Keynesian model of the business cycle. A model with nominal rigidities is extended by assuming that a fraction of firms need to borrow money to pay their wage bill. Hence, monetary policy tightenings increase effective unit labor costs of production, and might imply an increase in inflation. The model explains the joint dynamics of output, inflation, real wages, and interest rates, and is estimated using a Bayesian framework and data for the United States and the euro area. The main result is that cost channel effects are absent in both cases. Moreover, it is not possible to obtain a "price puzzle" type of behavior from estimated impulse responses to monetary policy shocks.